Training The Utilization Of Palm Oil Waste Supporting Village Community Economy - Desi Fitria; Iswidana Utama Putra; Dennis Rydarto Tambunan; Melly Susanti (International Journal of Science, Technology & Management, 2021)
There are still a lot of environmentally friendly waste that has not been used. Like palm oil fronds that rot because they are not used. This is due to the lack of knowledge about the benefits of oil palm frond waste. The purpose of this research is to provide insight to the community about processing oil palm frond waste, through training. Specifically, this study aims to measure the level of training in the utilization of palm oil frond waste against the results of activities in making products from environmentally friendly waste. It is hoped that this research can help the farming community in utilizing palm oil frond waste into a high-value product. The research sample consisted of 25 members of community organizations (PKK women's groups and youth youth groups). The method used is true experimental design by conducting training on the manufacture of products from oil palm frond waste. The results show that the informant independent variable (X1) has a significance of 0.175, material (X2) has a significance of 0.099, facilities (X3) has a significance of 0.956, behavior (X4) has a significance of 0.000. and innovation (X5) significance of 0.397. The significance value of the F test is 0.000. and all variables have an effect on Activity Results (Y). However, when tested individually, the behavior variable accepts the hypothesis while other independent variables reject the hypothesis. there are still many influences from other variables (R Squre = 66.7%) that affect the results of activities. Further research can use other methods, to find the effect of training on the results of activities.